Lenalidomide efficacy in activated B‐cell‐like subtype diffuse large B‐cell lymphoma is dependent upon IRF4 and cereblon expression. (18th December 2012) - Zhang, Ling‐Hua; Kosek, Jolanta; Wang, Maria; Heise, Carla; Schafer, Peter H.; Chopra, Rajesh
Summary Durable responses with lenalidomide monotherapy have been reported in patients with non‐Hodgkin lymphoma. In relapsed/refractory diffuse large B‐cell lymphoma (DLBCL), higher responses were observed in the activated B‐cell‐like (ABC) subtype than in the germinal centre B‐cell‐like subtype. Herein, the molecular mechanisms involved in the differential efficacy of lenalidomide in DLBCL subtypes were investigated. Using DLBCL cell lines, lenalidomide treatment was found to preferentially suppress proliferation of ABC‐DLBCL cells in vitro and delay tumour growth in a human tumour xenograft model, with minimal effect on non‐ABC‐DLBCL cells. This tumouricidal effect was associated with downregulation of interferon regulatory factor 4 (IRF4), a hallmark of ABC‐DLBCL cells. IRF4 inhibition by lenalidomide induced downregulation of B‐cell receptor (BCR)‐dependent NF‐κB. Whereas IRF4‐specific small, interfering RNA mimicked the effects of lenalidomide reducing NF‐κB activation, IRF4 overexpression enhanced NF‐κB activation and conferred resistance to lenalidomide. These findings indicate the crucial role of IRF4 inhibition in lenalidomide efficacy in ABC cells. Furthermore, lenalidomide‐induced IRF4 downregulation required the expression of cereblon, a molecular target of lenalidomide. Taken together, these findings suggest that lenalidomide has direct antitumour activity against DLBCL cells, preferentially ABC‐DLBCL cells, by blocking IRF4 expression and the BCR‐NF‐κB signalling pathway in a cereblon‐dependent manner.